Universal War Strategy Supported Political Integration Reviewed from The Third Sila Pancasila; The Unity of Indonesia - Agus Setyo Hartono (Journal of Social Science, 2021)
The understanding of uniting the nation's cultural diversity requires a strategy in handling it so that it does not become a breaker of Indonesian unity, in the political integration of diversity in party groups and their partisanship with government power, it becomes less and less pro to certain communities in society that are represented in dealing with various problems. Cultural diversity that characterizes the Indonesian nation is a nation's wealth or asset that must be preserved and it is hoped that it will lead to potential excellence in the world. Conflicts that are oriented towards division, disintegration of the nation, and want to liberate from the unitary republic of Indonesia require concrete efforts to be overcome for the sake of realizing national unity in the Universal War Strategy. Therefore, the researcher wants to examine how the implementation of a sense of unity and political integration as an element that plays a very important role in the universal war strategy, because the understanding of universal war in the face of non-military threats is needed from government agencies outside of defense, especially in the political dimension, so civic, universality and populist is a feature of the settlement with a universal war strategy.